Analytical, numerical and experimental studies on the Semi-Active Friction Tendon - Garrido, Carlos Hernán (2017)
For controlling vibrations, a Semi-Active Friction Tendon (SAFT), which consists of a semi-active friction damper and an auxiliary spring that are linked to the structure by a cable, is studied experimentally, numerically and analytically. Two semi-active control laws are implemented, one is based on velocity feedback (denoted as SQDCL) and the other is based on force feedback (denoted as SPCL); the passive control case is also studied for comparison. Based on the structural displacement reduction and the hysteretic behavior assessment, it is clearly demonstrated that (for SAFTs with a given pre-tension force): (1) the effectiveness of the optimized passive-control case can always be improved by using semi-active control with any of the two control laws; and (2) the SPCL is more effective for large displacements, while the SQDCL is more advantageous for very small displacements. Moreover, closed-form expressions for the dissipated energy are presented for the three cases under consideration, which can be used in preliminary design of SAFTs to decide between passive and semi-active control and to choose the more suitable control law.